Exploring the Dynamics of Doshas a Research-Based Review on Kriya Sharir (AYUSHDHARA, 2025)
The concept of Doshas- Vata, Pitta, and Kapha- is fundamental to Ayurvedic medicine and is vital for maintaining the balance and overall health of the human body. In Ayurvedic philosophy, these three Doshas influence not only physical functions but also mental and emotional health. The balance between these doshas affects various health aspects, including metabolic activities, immune response, mental clarity, and emotional stability. Kriya Sharir, which focuses on the study of bodily functions and physiological systems, provides insights into the interaction of Doshas, their functioning within the body, and the implications of any imbalances that may arise. This review examines the complex relationships between Doshas, their regulatory roles in bodily systems, their effects on disease development, and the clinical relevance of maintaining Dosha equilibrium. By integrating ancient Ayurvedic texts with modern scientific findings, it explores the influence of Doshas on various physiological activities, including digestion, metabolism, elimination, circulation, and neurological functions. Furthermore, the paper investigates how imbalances in Doshas can lead to the onset of diseases and disorders, underscoring the holistic approach of Ayurvedic treatments designed to restore balance. Through a thorough analysis of relevant classical and contemporary literature, this paper emphasizes the significance of understanding doshas within Kriya Sharir as a foundation for personalized healthcare. It also aims to present evidence-based insights into Ayurvedic perceptions of health and disease, thereby enhancing appreciation for dosha dynamics and their relevance in modern health practices. Additionally, the research highlights potential areas for future studies that bridge traditional Ayurvedic knowledge with contemporary medical science, advocating for integrative strategies in health management and disease treatment.